PARADIGMA FIQIH SOSIAL KH ALI YAFIE - Moh Dahlan (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
This study aims to examine the social fiqh paradigm of KH Ali Yafie which is formulated as follows: what is the historical existence of social fiqh paradigm of KH Ali Yafie in Indonesia? how is the development of social fiqh paradigm of KH Ali Yafie in Indonesia? Using the ushul fiqih scholarship framework, this study concludes that First, the historical existence of KH Ali Yafie’s thought developed from the tradition of moderate pesantren scholarship, so that his struggle remained within the line of moderate Islamic movements within the Nahdlatul Ulama, to the top post, Rais Aam PBNU. Similarly his role in MUI. Although moderate, but firm stance also remains firmly proven KH Ali Yafie resigned from Pjs. Rais Aam PBNU because of differences in legal views with KH Abdurrahman Wahid. Second, the thought of fiqh KH Ali Yafie contributed not less because he has given solutions that  others do not think  of, such  as how to make  the sciences of history  and  natural sciences as a knife of analysis in studying the law of fiqih. Similarly his strongly  proven national- ism attitude puts  the fatwa of KH Hasyim  Asy’arie on the obligation to defend the state  as a legal fatwa which  must  be ignored by Muslim scholars and Muslims